Evaluation of Effect of Median U-Turns on Multilane Primary Highway Capacity in Thailand through Traffic Micro-Simulation Models - Ladda Tanwanichkul; Wuttikrai Chaipanha; Jumrus Pitaksringkarn (My University, 2018)
This article aims to analyze the effect of median U-turns and estimate the capacity of primary highways in Thailand using a traffic micro-simulation model.Six-lane and four-lane primary highways were selected for the study.The base condition results determined that the maximum capacity of a six-lane primary highway was 2,130 passenger cars/hour/lane, while the four-lane primary highway capacity was recorded as 2,194 passenger cars/hour/lane.Both results were slightly higher than those of the HCM2010 approach.Under prevailing conditions, both sections exhibited lower capacities than the HCM results by approximately 33.7% and 19.8% for the six-lane and fourlane primary highways, respectively, causing the impact of the median U-turn and highway characteristics in Thailand to directly affect traffic and driving behavior.Using the micro-simulation results, an equation was also regressed for estimating the capacity resulting from the impact of the median U-turns and heavy vehicles.These results may be used as guidelines for the design and analysis of multilane highways in Thailand.
Keywords: Primary (astronomy); Traffic Prediction and Management Techniques